Teampal ID (E-Commerce Paket Beternak Dan Pengembangan Budidaya Ternak) - Widiastra, I Gede Pageh; Eka Putra, I Gede Juliana; Fredlina, Ketut Queena (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
The acceleration of the economy in Indonesia can be seen from the increasing number of MSMEs in the culinary sector which has an impact on the need for protein consumption ingredients. On the other hand, the income of these needs is lacking because many farmers have difficulty getting capital to continue their business due to lack of information about access to capital. This research is a design and implementation of a livestock e-commerce system using the prototyping method. This research was carried out with 4 main stages, namely (1) communication stage, (2) quick plan and quick design modeling stage, (3) construction of prototype stage and (4) deployment delivery & feedback stage. In the design and implementation process, this research was developed with several technologies including Boostrap, Laravel, JavaScript and MySQL as the main database. The results of this research are expected to function properly to increase the productivity of the implementation of the e-commerce system for the livestock industry at Teampal Id startup.Keywords:  Animal Husbandry; E-Commerce; Laravel; Prototyping; Implementation AbstrakPercepatan perekonomian di Indonesia dapat dilihat dari meningkatnya jumlah UMKM di sektor kuliner yang memiliki impact pada kebutuhan bahan konsumsi protein. Disisi lain, pemasukkan kebutuhan tersebut kurang karena banyak peternak yang kesulitan mendapatkan modal untuk melanjutkan usaha dikarenakan masih minim informasi mengenai akses permodalan. Penelitian ini merupakan perancangan dan implementasi sistem e-commerce peternakan menggunakan metode prototyping. Penelitian ini dilaksanakan dengan 4 tahapan utama, yakni (1) tahap comunication, (2) tahap quick plan dan modeling quick design, (3) tahap construction of prototype dan (4) tahap deployment delivery & feedback. Pada proses perancangan dan implementasi, penelitian ini dikembangkan dengan beberapa teknologi diantaranya seperti Boostrap, Laravel, JavaScript dan MySQL sebagai database utama. Hasil dari penelitian ini diharapkan dapat berfungsi dengan baik untuk meningkatkan produktivitas implementasi dari sistem e-commerce bagi industri peternakan pada startup Teampal Id.